Synthesis of bifunctional Lipoxin-derived Enzyme-Triggered CO-Releasing Molecules (LipET-CORMs) - Hemmersbach, Lars; Adam, Ruth; Plevnali, Christina; Zhang, Xinmiao; Yard, Benito A.; Schmalz, Hans-Günther (European journal of organic chemistry, 2023)
Abstract In an attempt to develop new anti-inflammatory agents which act by co-release of carbon monoxide (CO) and a specialized pro-resolving mediator, we designed conjugates of a lipoxin A4 analogue and an acyloxycyclohexadiene-Fe(CO)3 complex as an esterase-triggered CO-releasing molecule (ET-CORM). After adjustment of the protecting group strategy, two of such compounds were successfully prepared by total synthesis (12 steps; 4?5?% overall yield) starting from deoxy-d-ribose and exploiting a Wittig olefination and an intermolecular Heck reaction as key C?C bond-forming steps. A crucial late reduction of an aryl-ketone moiety in the presence of a highly sensitive dienol ester functionality was achieved with BH3-SMe2 in the presence of catalytic amounts of NaBH4. Both target compounds were dose-dependently toxic towards cultured human umbilical vein endothelial cells (HUVEC), with LipET-CORM 1-A being slightly more toxic. While induction of heme oxygenase 1 (HO-1) in HUVEC was observed for both compounds, they did not inhibit TNF-α-mediated VCAM-1 expression in these cells. In M2 polarized macrophages HO-1 expression was more pronounced as compared to M1 polarized macrophages. In both types of macrophages HO-1 expression was downregulated by lipopolysaccharide, but only in M2 macrophages HO-1 expression was rescued by LipET-CORM. 15-Lipoxygenase (15-LO) was only expressed in M2 macrophages and was not influenced by LipET-CORM. Collectively our data demonstrate that LipET-CORMs induce HO-1 expression in endothelial cells and M2 polarized macrophages. The role of the intra-cellular released lipoxin A4 in resolution of inflammation, however, remains to be assessed.
Online veröffentlicht: 20. Januar 2023
Gesehen am 04.09.2024